2012
DOI: 10.22610/jebs.v4i6.335
|View full text |Cite
|
Sign up to set email alerts
|

How Leadership Behaviors Affect Organizational Performance in Pakistan

Abstract: The purposes of this study are to analyze which leadership behavior is most closely related with organizational performances based on both leader’s and employee’s perceived; and to what extent leadership behaviors have impact on organizational performances in public and private organizations. Two questionnaires were developed to capture leaders’ behaviors and employees’ responses. Sample comprises of five hundred managers and five hundred employees of different private and public sector organizations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The findings of the study established that an unfair tax system, poor administration of the taxation system, inefficient and corrupt employees, and lack of effective governance of the taxation system increase the tax evasion attitude of individuals. Previous studies e.g., Akram et al (2012) found a strong relationship between tax evasion and the taxation system. They found that an inefficient and unfair tax system is one of the main causes of tax evasion attitudes of individuals.…”
Section: Tr4mentioning
confidence: 72%
See 2 more Smart Citations
“…The findings of the study established that an unfair tax system, poor administration of the taxation system, inefficient and corrupt employees, and lack of effective governance of the taxation system increase the tax evasion attitude of individuals. Previous studies e.g., Akram et al (2012) found a strong relationship between tax evasion and the taxation system. They found that an inefficient and unfair tax system is one of the main causes of tax evasion attitudes of individuals.…”
Section: Tr4mentioning
confidence: 72%
“…In the existing literature, the tax system is revealed as a significant determinant of tax evasion attitude. Akram et al (2012) found a strong relationship between TE and TS. The findings show that TS in the country contributes positively toward TPs' perspective and stimulates evasion behaviors.…”
Section: Tax System (Ts) and Tax Evasionmentioning
confidence: 92%
See 1 more Smart Citation
“…For the dictatorial (autocratic/authoritarian) leadership style, some studies indicated that it has a negative impact on employee performance (Basit et al, 2017;Iqbal et al, 2015;Nasir, Nordin, Seman & Rahmat, 2014;Ayene, 2016). However, other studies found a positive correlation between dictatorial leadership and employee performance (Chua et al, 2018;Akram et al, 2012;Bakwai, 2015;Bhargavi & Yaseen, 2016;Khajeh, 2018;Wang & Guan, 2018). The contradiction gap between one group of studies and another warranted further research, among other gaps.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Leadership behavior is often associated with rewards to innovative workers and/or punishment for failing to deliver (Elenkov, 2012;Jong and Hartog, 2007;Li-Fei and Hua, 2010;Obiwuru et al, 2011;Stoffers and Heijden, 2009;Wanga et al, 2011;Zaccaro and Klimoski, 2011). Visionary leadership behavior is linked to providing guidelines for future engagements and communicating both the desired types of innovation and a clear vision (Akram et al, 2012). Visionary leaders are also recognized by their ability to engage women and promote gender diversity and inclusion allowing women to be equal partners in the growth of an organization (Elsaid and Eahab, 2012).…”
Section: Leadership Behavior Employee Performance Management and Organizational Innovationmentioning
confidence: 99%